Palliative care evidence review service (PaCERS): a rapid systematic approach to identifying high quality evidence on palliative care. Issue 3 (1st September 2016) - Gee, Peter; Woodward, Amanda; Nelson, Annmarie; Mann, Mala; Byrne, Anthony
Abstract : Introduction: The importance of relating clinical practice more closely to evidence, is recognised by health and social care professionals and commissioners alike. However a significant obstacle is the lack of time to locate and read the relevant literature. Additionally, the expectation to assess quality and deal with conflicting information can be challenging. Therefore, we have initiated PaCERS to support professionals and other decision makers working in palliative care. Aim: The aim of this service is to conduct rapid evidence reviews on questions of current and direct importance to clinical care or service delivery, producing critically appraised summaries of available evidence, in the shortest possible timeframe. Responding directly to external clinical/organisational calls for evidence, the service will also facilitate at-pace integration of research findings into service development, and will help to embed palliative care research into clinical practice. Method: The service will enable palliative care professionals to gain an overview of literature relevant to the topic of immediate interest in order to inform future practice/service design, confirm that current practice reflects contemporary research evidence and identify areas that require further research. A web-based repository of all reviews produced through PaCERS will be made available to palliative care decision makers. Results: We have held a highly productive workshop with clinical colleagues to refine our processes and achieve consensus on how best PaCERS can serve the palliative care community. One full review, which identifies best practice models for end of life and palliative care in rural areas, has been completed. Conclusion: This service will impact directly on palliative care clinicians and other decision makers, and indirectly on patients/carers in receipt of palliative care. This research evidence review service can provide guidance for a variety of palliative care issues including round the clock palliative care.